Impact of Chronic Kidney Disease on Outcomes of Patients with Gastrointestinal Bleeding and Concomitant Cardiovascular Disease: A Multicentred Prospective Study - Muhammad Zubair, Amir Ali, Kantash Kumar, Effat Zahrah, Mehreen Kamran, Muhammad Naeem, Jateesh Kumar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic kidney disease (CKD) is a prevalent systemic disorder that increases the risk of bleeding and adverse cardiovascular outcomes. Objective: To evaluate the impact of CKD on outcomes in patients presenting with gastrointestinal bleeding and concomitant cardiovascular disease. Methodology: This was a cross-sectional multicenter study conducted at Sahiwal Teaching Hospital, Sahiwal from March 2023 to August 2023, included 185 patients admitted with gastrointestinal bleeding and established cardiovascular disease. Patients were categorized into two groups: those with CKD (n = 95) and those with normal renal function (n = 90). Data on demographics, comorbidities, laboratory findings, transfusion requirements, rebleeding rates, hospital stay, and mortality were recorded. Results: The mean age of the study population was 61.8 ± 10.7 years, with a male predominance (60.5%). CKD patients had significantly lower hemoglobin levels (8.3 ± 2.0 g/dL vs. 9.6 ± 2.4 g/dL, p = 0.001) and higher rates of hypertension, diabetes, and ischemic heart disease. Rebleeding occurred in 22.1% of CKD patients compared to 7.8% of non-CKD patients (p = 0.007). Blood transfusions were required in 69.5% versus 43.3%, respectively (p < 0.001). The mean hospital stay was longer in CKD patients (8.2 ± 3.6 vs. 5.7 ± 2.8 days, p < 0.001), and mortality was significantly higher (13.7% vs. 5.6%, p = 0.04). Multivariate analysis revealed that CKD (OR: 2.61, 95% CI: 1.11–6.15), low hemoglobin (OR: 1.83, 95% CI: 1.02–3.64), and diabetes mellitus (OR: 1.97, 95% CI: 1.05–3.98) were independent predictors of mortality. Conclusion: CKD significantly worsens the prognosis of patients with gastrointestinal bleeding and cardiovascular disease. These patients experience higher mortality, rebleeding rates, and transfusion needs, along with prolonged hospitalization. Keywords: CKD, gastrointestinal bleeding, cardiovascular disease, mortality, rebleeding, transfusion, renal impairment